ANALYSIS OF THE PRACTICE OF FINANCING THE GREEN ECONOMY IN DEVELOPING COUNTRIES - Raimzhanova Madina Asrarovna; Zokirova Feruza Farkhod kizi (Modern American Journals, 2025)
This article analyzes the analysis of the practice of financing the green economy in developing countries. At present, when the world economy is gradually transforming into a low-carbon one, the criterion of sustainable development of the "green" economy is becoming an increasingly decisive factor in the competitiveness of the state. At the same time, aggressive business development, especially in relation to lending and investment, often opposes environmental protection issues. The purpose of the article is to study the practice of "green" finance in developed countries and identify development prospects in the Republic of Uzbekistan.